Sell like a team the blueprint for building teams that win big at high-stakes meetings - Dalis, Michael (McGraw Hill-Ascent Audio, 2017)
Build a championship sales team that prepares, practices, and plays in sync-and closes every deal Gone are the days of meeting a client for lunch, chatting about your product, and closing the sale over dessert. Buyers today look very differently from those of the past. They make networked purchasing decisions by committee, with diverse roles, interests and backgrounds. With access to more information and a greater ability to share it, they demand value, access and alignment from their counterparties. Sales is now a team sport, and to win you have to build and manage selling squads that work in complete alignment-not just during client meetings, but before and after, as well. In Sell Like a Team, Michael Dalis, a senior consultant at the legendary sales training firm, The Richardson Company, guides you through the process of creating and managing selling squads that execute and win in every sales meeting or pitch. Winning selling squads are fueled by trust. There is an effective leader and every member knows his or her role. They plan, practice and make adjustments together. During customer meetings, they execute as a unit. And afterward, they debrief together so they can advance the sale, replicate the high points and eliminate the low ones in future meetings. In today's competitive market, the difference between the winner and all the others is a lean at the tape. There's a world of difference between teams that are qualified and those that win. This groundbreaking guide provides everything you need to create and organize selling squads that win more and win big.
Online resource; title from title details screen (O'Reilly, viewed September 27, 2022)
Keywords: Selling; Teams in the workplace; Sales meetings; Vente; Équipes de travail; Réunions de vente; selling; Downloadable audio books; Audiobooks; Livres audio